2019
DOI: 10.1097/pai.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 Gene Expression in Fine-needle Aspiration Samples of Thyroid Nodules as a Marker for Preoperative Diagnosis of Thyroid Cancer

Abstract: There is a great interest in molecular markers that would help in the preoperative diagnosis of malignant thyroid nodules in cases of indeterminate fine-needle aspiration cytology. The aim of this study was to determine the diagnostic accuracy of HMGA2 gene expression in discriminating benign from malignant thyroid nodules. In this study, 237 preoperative thyroid fine-needle aspiration samples were analyzed prospectively for the expression of the HMGA2 gene by real-time reverse transcription polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Remaining 9 full‐text articles were assessed for eligibility, and 2 articles were excluded due to insufficient data for the calculation of sensitivity and specificity of HMGA2 gene expression in patients with thyroid nodules. Finally, 7 studies (10 results) were selected and were eligible for the systematic review and meta‐analysis and no additional studies were found screening the references of these articles . The characteristics of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Remaining 9 full‐text articles were assessed for eligibility, and 2 articles were excluded due to insufficient data for the calculation of sensitivity and specificity of HMGA2 gene expression in patients with thyroid nodules. Finally, 7 studies (10 results) were selected and were eligible for the systematic review and meta‐analysis and no additional studies were found screening the references of these articles . The characteristics of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of all 7 studies, 6 studies enrolled patients retrospectively . Two studies used formalin‐fixed paraffin‐embedded (FFPE) thyroid tissue for HMGA2 gene expression scan, and 2 studies used fine‐needle aspiration biopsy (FNAB) samples of thyroid tissue. Other 3 studies used both of FFPE and FNAB samples of thyroid tissue .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations